Direct Pulp Capping with Condenses and Adhesive Restoration on Fracture Teeth with Pulp Exposure - Junji, TAGAMI; Norimichi, INAI; Nobuhiro, KATAHIRA (The Japanese Journal of Conservative Dentistry, 2020)
Purpose: The direct pulp capping procedure is performed when the dental pulp is accidentally exposed. In this case report of pulp exposure caused by fracture, direct pulp capping using MTA and attachment of the tooth fragment was applied and the prognosis was followed-up. Case: A 32-year-old female patient presented with the upper right central incisor horizontally fractured in approximately half of the crown, with pulp exposure, mild spontaneous pain and cold-water pain. Chemical treatment of the exposed pulp surface was performed, and MTA was lightly pressed to the exposed pulp. Subsequently, a self-etching primer was used on both the residual dentin and the fragment, and finally they were bonded to each other with flowable composite resin. The prognosis after 3 weeks, 3 months and 6 months was good. Long-term follow-up observation of this case is planned. Conclusions: An excellent clinical prognosis was obtained with direct pulp capping in traumatic teeth using MTA compressed toward the pulp side, combined with adhesive attachment of the tooth fragment to prevent microleakage. Protection of the pulp and esthetic restoration were achieved simultaneously with this technique.